Temuan Ketidaktepatan Penggunaan Ejaan Huruf dalam Surat Dinas Kantor Camat Kuranji, Padang - Shinta Amelia Putri; Noviatri Noviatri; Leni Syafyahya (Puitika)
This research is motivated by the identification of the phenomenon of inaccuracies in spelling usage within official correspondence from the Kuranji Subdistrict Office in Padang. Consequently, the aim of this study is to describe these spelling inaccuracies. To address this issue, the research is structured into three distinct phases, namely data collection, data analysis, and presentation of the data analysis results. In the data collection phase, the employed methodology and techniques consist of the observational method using the basic technique of direct observation, complemented by the advanced technique of unobtrusive observation. In the data analysis phase, the utilized methodology and techniques involve referential and orthographic matching methods, utilizing the fundamental technique of Element Determination Sorting (EDS) along with the advanced techniques of Differentiating Comparative Analysis (DCA) and Equating Comparative Analysis (ECA). Subsequently, in the presentation of the data analysis results phase, both formal and informal methods are employed. Based on the analysis results, inaccuracies in letter spelling usage were identified, encompassing the misuse of capital letters, italics, and bold letters.